Patients discharged before and after presence of medical emergency specialists - Shahrokh Yousefzadeh chabok; Zahra Mohtasham Amiri; Zahra Haghdoost; Mina Mohseni; Peyman Asadi; Ehsan Kazemnezhad Leili (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Emergency Department (ED) is the most important ward of hospital which its function can have enormous effect on function of other wards and patients' satisfaction. One of the most important criteria in evaluation of ED is the duration of time spent by patients for receiving diagnostic and treatment services. Prolonged waiting and visiting time in ED reduce the quality of care and increase the adverse events. Objective: This study aimed to determine number of patients discharged in less than 6 hrs before and after presence of medical emergency specialists. Methods: This cross-sectional study was conducted on hospitalized patients three months before and after the presence of EM specialists in Poursina Educational-therapeutic Hospital from September 2009 to March 2010 and patients' condition was assessed considering the variable of discharge in less than 6 hours. Data were collected by hospital information system (HIS) and analyzed using chi-square statistical method and logistic regression model. Results: Findings of this study showed that only 856 patients (15.54%) of all hospitalized patients in ED (5506) were discharged in less than 6 hours 3 months before the presence of EM specialists. However, this rate increased from 5271to 1621 (30.75%) in first three months after presence of EM specialists in ED. According to regression model there was a significant association between presence of EM specialists and percent of patients discharged in less than 6 hours (P< 0.0001). Conclusion: By on time diagnosis and treatment waiting time and hospital stay can be decreased and patient satisfaction increased. Therefore for prevention of wasted time in diagnosis and patient treatment it is suggested to provide opportunities that ED could benefit from continuous ED specialists' care.